Porous spherical NiO@NiMoO4@PPy nanoarchitectures as advanced electrochemical pseudocapacitor materials - Yi, Ting-Feng; Qiu, Li-Ying; Mei, Jie; Qi, Si-Yu; Cui, Ping; Luo, Shaohua; Zhu, Yan-Rong; Xie, Ying; He, Yan-Bing (Science bulletin (Beijing), 2020)
[Display omitted] In this work, a rational design and construction of porous spherical NiO@NiMoO4 wrapped with PPy was reported for the application of high-performance supercapacitor (SC). The results show that the NiMoO4 modification changes the morphology of NiO, and the hollow internal morphology combined with porous outer shell of NiO@NiMoO4 and NiO@NiMoO4@PPy hybrids shows an increased specific surface area (SSA), and then promotes the transfer of ions and electrons. The shell of NiMoO4 and PPy with high electronic conductivity decreases the charge-transfer reaction resistance of NiO, and then improves the electrochemical kinetics of NiO. At 20Ag−1, the initial capacitances of NiO, NiMoO4, NiO@NiMoO4 and NiO@NiMoO4@PPy are 456.0, 803.2, 764.4 and 941.6Fg−1, respectively. After 10,000 cycles, the corresponding capacitances are 346.8, 510.8, 641.2 and 904.8Fg−1, respectively. Especially, the initial capacitance of NiO@NiMoO4@PPy is 850.2Fg−1, and remains 655.2Fg−1 with a high retention of 77.1% at 30Ag−1 even after 30,000 cycles. The calculation result based on density function theory shows that the much stronger Mo-O bonds are crucial for stabilizing the NiO@NiMoO4 composite, resulting in a good cycling stability of these materials.